A Comparative Legal Analysis of the Fundamental Human Rights Enshrined in Nigeria and Uganda Constitutions - John, Damina Joshua; Maifada, Khadijat Ibrahim; Okonji, Ifesinachi Charles; Onwubiko, Kelechi; Kisubi, Esther (NIU Journal of Humanities; Vol 9 No 3 (2024): NIU Journal of Humanities, Vol. 9 No. 3, September 2024, 2024)
What is now known today as Fundamental Human Rights came to lamb light through a United Nations declaration called the UDHR; Universal Declaration of Human Rights, of 1948. This document may have not been a legal instrument per se but a mere declaration for the world to follow. Because it was not an instrument to be relied on in Court when these rights were violated, there was a need for separate documents to be created and that led to the creation of two instruments out of it Known as ICCPR and ICESCR. These two legal instruments have been incorporated by Nigeria and Uganda with little variations adopted in their constitutions. It is concerning that this study seeks to educate readers through a comparative analysis of the fundamental human rights stipulated in the Nigeria and Uganda Constitutions to show their similarities and differences and if there are gaps make recommendations to fill them. Concerning this the study adopts a doctrinal method of research, utilizing primary and secondary sources. The study found that Nigeria and Uganda have recognized these rights and codified them under chapter four of their Constitutions, these rights are referred to as inalienable rights are they cannot be transferred, sold, or shared among citizens. The constitution of Nigeria and the constitution of Uganda guarantee their citizens protection of these rights where; violation will attract full punishment by the Law. However, there are core variations in these which in essence the Uganda constitutional rights seem to be more encompassing than the Nigerian rights provided for in the constitution. Hence this study concludes and recommends the need for Nigeria government to take a leap from the Uganda perspective of human rights as contain in their constitution. Keywords: Legal, Fundamental, Human, Rights, and Constitution.